Postgraduate in Geography (UPTC-IGAC): contributions to the geographical discipline in Colombia (1984-2019) - Rojas Corredor, Jorge Leonardo (Universidad Pedagógica y Tecnológica de Colombia, 2021)
This article reconstructs the track record of the Geography Graduate Program (EPG, for its acronym in Spanish), derived from the agreement between the Universidad Pedagógica y Tecnológica de Colombia (UPTC) and the Instituto Geográfico Agustín Codazzi (IGAC), based on the analysis of theses and dissertations written within the EPG. The primary technique is the documentary review, belonging to the qualitative approach, which provides greater depth and interpretative richness to the information obtained. The results include the definition of the main themes, methods, and geographic approaches that have guided the theses and dissertations published by the EPG, which, to a certain extent, reflect the interests and concerns of geography in Colombia between 1984–2019. This type of historiographic work contributes to systematizing local experiences in the discipline.